The Impact of Integrated Development of Agriculture and Tourism on Rural Ecological Environment Quality. (1st August 2022) - Wang, Jingjing; Zhou, Faming; Xie, Ailiang
Abstract : The integrated development of agriculture and tourism plays an important role on the rural ecological environment, which has not absorbed attention of the academic community. From the perspective of stakeholders, the impact mechanism of the agriculture and tourism integration on rural ecological environmental quality was analyzed. Based on three dimension-agricultural production environment, rural living environment, and rural environmental governance, the evaluation index system of rural ecological environment quality was constructed, and the multi-index comprehensive evaluation method was used to measure its level. The coupled system model of physics and entropy method were used to measure the degree of the integrated development level of agriculture and tourism industry. Based on data of 19 provinces in the Yangtze River Economic Belt and Yellow River Economic Belt in China from 2007 to 2019, static and dynamic panel models were used to examine the impact of agriculture and tourism integration on the quality of rural ecological environment and its mechanism. The results show that the integrated development of agriculture and tourism has a significant positive correlation with the quality of rural ecological environment, so the integrated development of agriculture and tourism can play a positive role in improving the quality of rural ecological environment. The rural ecological environment quality of the last period has a significant impact on the rural ecological environment quality of the current period, which indicates that the rural ecological environment quality has a strong inertia. Under the background of the current ecological civilization construction in China, the research result has significant theoretical and practical value.